Increasing competition and the winner's curse: Evidence from procurement - Han Hong; Matthew Shum (The Johns Hopkins University, Department of Economics, 2001)
We empirically measure the effects of increasing competition on equilibrium bidding in procurement auctions In common-value auctions the winner's curse counsels more conservative bidding as the number of competitors increases First we estimate the structural parameters of an equilibrium bidding model and test for the importance of common-value components in bidders' preferences Second we use these estimates to calculate the effects of increasing competition on both individual bids as well as winning bids ie procurement costs. We analyze bid data from construction procurement auctions run by the New Jersey transportation department Our results indicate that for a large subset of these auctions the median procurement cost rises as competition intensifies: increasing the number of bidders from 3 to 6 raises median procurement costs by about 15% In this setting then asymmetric information overturns the common economic wisdom that more competition is always desirable.
Keywords: 330; Auktionstheorie; Öffentliche Beschaffung; Wettbewerb; Schätzung; New Jersey